The effect of self-efficacy on performance with mediation of affective commitment in vocational schools throughout West Kalimantan - Fauzan, Rizky; Daud, Ilzar; Kalis, Maria Cristiana Iman; Lianto, Lianto; Rustam, Rustam (International research journal of management, IT and social sciences, 2023)
Quantitative approach, survey technique, analysis of statistical test data Partial Least Squares Path Modeling (PLS-SEM) Wrappls version 7, questionnaire data collection tool and documentation, population of 3,999 and sample of 254 teachers, 29 public and private SMKs, research locations (3) hinterland districts: Sanggau, Sekadau, Landak districts; (3) coastal districts: Sambas, Mempawah and Kuburaya districts; (2) the city of Pontianak and the city of Singkawang. From the results of the study it was found that self-efficacy towards affective commitment has a positive and significant effect, the hypothesis is in a unidirectional relationship and is able to enhance each other; Affective commitment to achievement is positive and significant, has a one-way relationship and is able to improve; self-efficacy on achievement through affective commitment has a positive and significant effect, the hypothesis is in a unidirectional relationship and is able to enhance each other. From this investigation it has been able to foster a new model of affective commitment and the development of the concept of achievement in SMKs throughout West Kalimantan.